2000
DOI: 10.1097/00004424-200004000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Lobar Distribution of Emphysema in Computed Tomographic Densitometric Analysis

Abstract: CT densitometry showed a distinct lobar distribution of emphysema. Pulmonary function is significantly different between predominantly upper- and lower-lobe emphysema groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
32
1
1

Year Published

2001
2001
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 16 publications
9
32
1
1
Order By: Relevance
“…Three studies are of special interest because they quantified emphysema automatically, based on the percentage of LAAs below a specified threshold. SAITOH et al [30] reported that FEV1/ FVC showed the strongest correlation with lower lobe emphysema distribution, but that the transfer factor of the lung for carbon monoxide showed the strongest correlation with upper lobe emphysema distribution. MAIR et al [28] showed that upper zone distribution of emphysema in COPD subjects was associated with a higher total score on the St George's Respiratory Questionnaire.…”
Section: Discussionmentioning
confidence: 99%
“…Three studies are of special interest because they quantified emphysema automatically, based on the percentage of LAAs below a specified threshold. SAITOH et al [30] reported that FEV1/ FVC showed the strongest correlation with lower lobe emphysema distribution, but that the transfer factor of the lung for carbon monoxide showed the strongest correlation with upper lobe emphysema distribution. MAIR et al [28] showed that upper zone distribution of emphysema in COPD subjects was associated with a higher total score on the St George's Respiratory Questionnaire.…”
Section: Discussionmentioning
confidence: 99%
“…Consistently, Gurney et al and Haragushi et al showed that the extent of emphysema had higher correlations with D L CO in the lower lung zone than in the upper lung zone, even though the upper lung zone was more severely affected by emphysema [68,69]. On the basis of the lobar distribution of emphysema as determined by CT, Saitoh et al reported that the airflow limitation, the residual volume, and the total lung capacity were higher in the predominantly lower-lobe emphysematous group than in the predominantly upper-lobe emphysematous group [70]. However, Nakano et al reported that the correlations between the RA 960 , and FEV1 or RV/TLC were higher in the lower lobes, but the correlation between RA 960 and D L CO was higher in the upper lobes.…”
Section: Comparison Between Ct Quantification and Pulmonary Function mentioning
confidence: 99%
“…Consistently, GURNEY et al [67] and HARAGUSHI et al [68] showed that the extent of emphysema had higher correlations with DL,CO in the lower lung zone than in the upper lung zone, even though the upper lung zone was more severely affected by emphysema. On the basis of the lobar distribution of emphysema as determined by CT, SAITOH et al [69] reported that the airflow limitation, the RV and the TLC were higher in the predominantly lower-lobe emphysematous group than in the predominantly upper-lobe emphysematous group. However, NAKANO et al [34] reported that the correlations between the RA960, and FEV1 or RV/TLC were higher in the lower lobes but the correlation between RA960 and DL,CO was higher in the upper lobes.…”
Section: Factors Influencing Computed Tomography Densitometrymentioning
confidence: 99%